2006
DOI: 10.1212/01.wnl.0000224760.22802.e8
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial plasma glucose excursions and cognitive functioning in aged type 2 diabetics

Abstract: Exaggerated postprandial glucose (PPG) excursions are associated with a derangement of both global, executive, and attention functioning. A tighter control of PPG may prevent cognitive decline in older diabetic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 34 publications
3
88
0
7
Order By: Relevance
“…We also found that patients with dementia had significantly higher PPG and lower FPG levels, whereas no differences were found for A1c compared with patients without dementia ( Table 1). These findings are to some extent in accordance with previous articles underlining that cognitive abilities are significantly poorer due to transient glucose excursions caused by treatment-induced hypoglycemia 18,19 or experimentally produced hyperglycemia. 20 Unfortunately, our protocol did not allow testing for glucose excursions.…”
Section: Discussionsupporting
confidence: 93%
“…We also found that patients with dementia had significantly higher PPG and lower FPG levels, whereas no differences were found for A1c compared with patients without dementia ( Table 1). These findings are to some extent in accordance with previous articles underlining that cognitive abilities are significantly poorer due to transient glucose excursions caused by treatment-induced hypoglycemia 18,19 or experimentally produced hyperglycemia. 20 Unfortunately, our protocol did not allow testing for glucose excursions.…”
Section: Discussionsupporting
confidence: 93%
“…16 Abbatecola et al 146 report a randomised trial comparing repaglinide and glibenclamide. The main outcome measure was cognitive function, with the hypothesis being the tighter control of postprandial PG would reduce cognitive decline, in patients aged 60-78 years, mean age 74 years.…”
Section: Evidence On Repaglinidementioning
confidence: 99%
“…In a study that randomly assigned 156 older patients with diabetes to two different oral anti-diabetic agents, higher postprandial plasma glucose excursions (less tight diabetes control) were associated with greater declines in cognitive performance measures over one year of follow-up. 9 An inverse correlation has been noted between some cognitive measures and hemoglobin A1c levels, also suggesting that worse glycemic control may be associated with greater cognitive decline.…”
Section: Resultsmentioning
confidence: 99%